FACTORS RELATED TO THE POTENTIAL ACCELERATION OF MENARCHE - Rima Novianti; Dila Ardila (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2021)
Menarche is the first period of menstruation that young women get when they reach puberty. According to RISKESDAS (2013), the average age of menarche is less than 12 years old. One of the issues is the lack of reproductive health knowledge, which is inversely linked to the openness of mass media that is freely available to adolescents. The goal of this study is to determine the factors that contribute to the potential acceleration of menarche age in Karawang adolescents. This research used a cross-sectional design with 391 research samples. Snowball Sampling and Simple Random Sampling are two sampling methodologies. The Chi-Square test with a degree of significance (0.05) was utilized in the univariate and bivariate analyses. The findings revealed a link between genetics (p: 0.000), adult mass media exposure (p: 0.004), first date (p: 0.000), socioeconomic status (p: 0.001), and nutritional status (obesity p: 0.000, normal p: 0.007, underweight p: 0.001) with the possible acceleration of menarche, although there is no link between overweight p: 0.760 and the possible acceleration of menarche age. Menarche is the first step towards a mature reproductive system with the younger menarche age, it is necessary to prepare the maximum knowledge about physical changes that occur in order for adolescents to prepare for their reproductive health and self-acceptance of the task of the next stage of development.